2010
DOI: 10.1210/en.2010-0355
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Natriuretic Peptides Associated with Lipid Accumulation in Cardiac Ventricle of Obese Mice

Abstract: Plasma B-type natriuretic peptide (BNP) and proBNP are established markers of cardiac dysfunction. Even though obesity increases the risk of cardiovascular disease, obese individuals have reduced plasma concentrations of natriuretic peptides. The underlying mechanism is not established. We used cultured cardiomyocytes and three different mouse models to examine the impact of obesity and cardiac lipid accumulation on cardiac natriuretic peptide expression. The cardiac ventricular expression of atrial natriureti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 35 publications
7
21
0
Order By: Relevance
“…When carbohydrate intake is reduced, energy must be supplied by other sources, like fatty acid oxidation, that require more oxygen [27, 28]. In our current study, mice fed a LCHF diet showed higher CD36 gene expression as well as higher levels of triglycerides in the myocardium [29, 30]. Similar cardiac alterations have been reported in obese mice fed a long-term high-fat diet [30].…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…When carbohydrate intake is reduced, energy must be supplied by other sources, like fatty acid oxidation, that require more oxygen [27, 28]. In our current study, mice fed a LCHF diet showed higher CD36 gene expression as well as higher levels of triglycerides in the myocardium [29, 30]. Similar cardiac alterations have been reported in obese mice fed a long-term high-fat diet [30].…”
Section: Discussionsupporting
confidence: 68%
“…In the present study the expression of the gene encoding natriuretic protein A (ANP) was significantly lower in the LCHF group. Increased ANP expression is traditionally used as a marker of heart failure [32, 33], but in recent years, decreases in ANP expression concomitantly with increases in the expression of its receptor, NPR-A, have been linked to metabolic dysfunction [29]. Abundant intake of dietary fat decreases ANP expression, and recent findings suggest that disturbances in the endogenous cardiac ANP/NPR-A system might induce cardiomyocyte hypertrophy [29, 32, 33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several other studies have used cardiac imaging to evaluate cardiac structure and mechanical function in db/db model. It appears that no consensus is established as some reports show cardiac hypertrophy with systolic and diastolic dysfunction [46,47], whereas others reported no change in cardiac function [20]. Discrepancies between some reports may be due to the duration and the type of diabetes, background mouse strain, gender and anesthesia.…”
Section: Discussionmentioning
confidence: 99%